A Comparative Study on Three Pioneer Methods for the Square Roots - Parajuli, Krishna Kanta (Nepal Journal of Mathematical Sciences, 2021)
During the classical period, the South Asian region had an illustrious history of mathematics, and it was regarded as fertile ground for the birth of pioneer mathematicians that produced a wide range of mathematical ideas and creations that made significant contributions. Among them, three creative personalities Bhaskaracarya, Gopal Pande and Bharati Krishna Tirthaji and their specific methods to find square roots are focused on this study. The analytical study of their methods is expressing in comparison with similarities, variety and simplicity. Each of the three mathematical treatise has its own formula for calculating the square roots. The Lilavati seems to have some effect upon the Vedic and Pande’s systems. In spite of having influenced by Lilavati, Gopal Pande disagreed on the problems regarding square roots and cube roots. To prove his point, Gopal Pande used the unitary method against the method described in Bhaskaracarya's famous book Lilavati. In the case of practicality and simplicity, the Vedic method is more practical, interesting and simpler to understand for the mathematics learners in comparison to the other two methods.